2016
DOI: 10.1371/journal.pone.0165952
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contribution of MHC Class II Genes in Susceptibility to West Nile Virus Infection

Abstract: WNV is a zoonotic neurotropic flavivirus that has recently emerged globally as a significant cause of viral encephalitis. The last five years, 624 incidents of WNV infection have been reported in Greece. The risk for severe WNV disease increases among immunosuppressed individuals implying thus the contribution of the MHC locus to the control of WNV infection. In order to investigate a possible association of MHC class II genes, especially HLA-DPA1, HLA-DQA1, HLA-DRB1, we examined 105 WNV patients, including 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…Sarri and coworkers identified HLA alleles responsible for susceptibility to WNV infection. They categorized HLA alleles to be either "protective," increased "susceptibility," or CNS-high risk [32]. None of the protective binding alleles suggested by Sarri et al were identified here.…”
Section: Discussionmentioning
confidence: 51%
“…Sarri and coworkers identified HLA alleles responsible for susceptibility to WNV infection. They categorized HLA alleles to be either "protective," increased "susceptibility," or CNS-high risk [32]. None of the protective binding alleles suggested by Sarri et al were identified here.…”
Section: Discussionmentioning
confidence: 51%
“…It is unclear at present whether these differences relate to the presence of alleles that protect from WND. An HLA-specific association for both protection and susceptibility to WND was suggested in previous studies (75)(76)(77). Additional research is needed to clarify whether such differences could discriminate patients with different disease outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we retrieved the results from our previous work [ 16 ] and focused on residues that form binding pockets P1, P4, P6, P7, P9 and P10. In the MHC class II heterodimer, chains α and β, both contribute to the formation of pockets P1, P6, P9 and P10 while chain β forms alone P4 and P7.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 105 confirmed WNV cases were used in our study. Sixty-eight individuals were reported with West Nile Neuroinvasive Disease (WNND) while thirty-seven individuals developed only mild symptoms and are referred to as West Nile Fever (WNF) cases [ 16 ]. Considering other risk factors in the populations under study, no sufficient information for immunosuppression of cases was available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation